Best practice in primary care pathology: review 7. Issue 5 (17th October 2006) - Smellie, W S A; Forth, J; Smart, S R S; Galloway, M J; Irving, W; Bareford, D; Collinson, P O; Kerr, K G; Summerfield, G; Carey, P J; Minhas, Rubin
Abstract : This seventh best-practice review examines four series of common primary care questions in laboratory medicine: (1) blood count abnormalities 2; (2) cardiac troponins; (3) high-density lipoprotein cholesterol; and (4) viral diseases 2. The review is presented in a question–answer format, with authorship attributed for each question series. The recommendations are a précis of guidance found using a standardised literature search of national and international guidance notes, consensus statements, health policy documents and evidence-based medicine reviews, supplemented by Medline Embase searches to identify relevant primary research documents. The recommendations are not standards, but form a guide to be set in the clinical context. Most are consensus based rather than evidence based. They will be updated periodically to take account of new information.